X-ray Diffraction and Magnetic Investigations of Lithium-Zinc Ferrites Synthesized by Electron Beam Heating; Journal of Electronic Materials; Vol. 47, iss. 2 - Surzhikov A. P. Anatoly Petrovich; Lysenko E. N. Elena Nikolaevna; Sheveleva E. A. Elena Aleksandrovna; Malyshev A. V. Andrei Vladimirovich; Astafyev A. L. Alexander Leonidovich; Vlasov V. A. Vitaliy Anatolievich (2018, 2018)
Title screen